Sharia Bank Cus Customer Loyalty Of Sharia Bank Banjarmasin City: Religiosity And Trust - irpan, muhammad irpan (Jurnal Ilmiah Ekonomi Islam, 2024)
Islamic banks should attract the interest and loyalty of their customers, by providing a sense of security and instilling customer trust in the bank. Most customers of Islamic banks are Muslims because it is related to the beliefs of Muslims to carry out Islamic teachings kaffah including in economic affairs. However, if the bank is Sharia. If Sharia banks are only limited to Muslim customers, it will hinder the development of the bank, then Sharia banks must be able to attract customers, both Muslims and non-Muslims. This study examines the loyalty of Islamic bank customers from the role of customer religiosity and trust. This research was conducted on Sharia bank customers in the city of Banjarmasin with a random sampling method, data collected through questionnaires, and hypothesis proof using Structural Equation Modeling– Partial Least Square (SEM – PLS) analysis. The test results stated that religiosity had a significant effect on trust; religiosity has a significant effect on loyalty; trust has a significant effect on loyalty; and religiosity has a significant effect on loyalty through trust